Time travel of older people through virtual reality: a qualitative study - Leyla Muslu; Zeynep Karakuş; Ercan Asï; Rabia Bayindir; Zeynep Özer (BMC Geriatrics)
Abstract Background Innovative technologies such as virtual reality may improve physical and cognitive functions in older people. While there are some experimental studies on virtual reality, qualitative studies related to the virtual reality experiences of older people are limited in the literature. This study aims to describe older people’s perceptions about their experiences regarding virtual reality. Methods The study has qualitative descriptive design. The data were collected through semi-structured individual interviews with older people (n = 37). The interviews were conducted during a two-months period, from February to March 2022. Thematic and descriptive analysis was used to analyse data. The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was used to report the study. Results Four themes and 15 sub-themes were identified from the interviews. The themes were (a) time travel through virtual reality, (b) comparing the past and present through virtual reality, (c) benefits of virtual reality, and (d) the meaning of virtual reality. Conclusions This study provides in-depth information about the views of older people regarding the virtual reality experience. The study revealed that older people had positive experiences with virtual reality and showed that it has the potential to be useful in elderly care. In the study, virtual reality also enabled older people to have a time-traveling experience. It is recommended that virtual reality should be integrated into the care of older people by nurses and healthcare professionals.